Stochastic assessment of the secular dynamics of the seasonal distribution of daily precipitations by the example of observations in Kiev - Kovalchuk, L.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
By means of the generalized normal three-parameter distribution (Generalized Gaussian 2), the secular dynamics of the statistical distributions of daily precipitations is seasonally recreated, and a tendency of probabilities of their categories is traced. It is found that the probability of extremely low rainfalls during the summer seasons increased from 0.39 to 0.62 and, conversely, fell from 0.58 to 0.33 during in the winter seasons. Comparable trends are characteristic of extremely high rainfalls in winter seasons, when their probability grew from 0.08 to 0.22, and in the summer and autumn seasons decreased. The intensity of precipitations in the normal range grew slightly during the year, except summer. Precipitations above or below the norm had no significant secular trends.